The Influence of Auditory Learning Style on Learning Motivation of Grade 6 Students at MINU Romli Afifah, Tajinan Regency - Budiansyah, Bimo Nugroho; Mardhatillah, Mardhatillah; Persada, Yuris Indria (Jurnal Ilmiah Teunuleh, 2024)
One of the internal factors that determines the success or failure of the teaching and learning process is learning motivation. In teaching and learning activities, of course, learning styles are involved to motivate students to learn. This study aims to analyze the effect of auditory learning styles on the learning motivation of grade 6 students at MINU Romli Afifah, Tajinan Regency. The research method used in this study is quantitative using purposive sampling data collection techniques consisting of 24 students from grade 6. The results of this study indicate that there is a significant influence between auditory learning styles on student learning motivation, with a coefficient of determination (R²) of 0.313 and a significant value (p-value) of 0.059. This identifies that auditory learning styles are one of the factors that influence student learning motivation.